2014
DOI: 10.1186/1756-0381-7-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between mitochondrial genetic variation and cardiovascular-related traits to develop a framework for mitochondrial phenome-wide association studies

Abstract: BackgroundMitochondria play a critical role in the cell and have DNA independent of the nuclear genome. There is much evidence that mitochondrial DNA (mtDNA) variation plays a role in human health and disease, however, this area of investigation has lagged behind research into the role of nuclear genetic variation on complex traits and phenotypic outcomes. Phenome-wide association studies (PheWAS) investigate the association between a wide range of traits and genetic variation. To date, this approach has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Early studies of the National Human Genome Research Institute GWAS Catalog revealed extensive pleiotropy among the common variants associated with complex traits. Many such examples have since been replicated and annotated in traditional epidemiologic and contemporary clinical collections [21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…Early studies of the National Human Genome Research Institute GWAS Catalog revealed extensive pleiotropy among the common variants associated with complex traits. Many such examples have since been replicated and annotated in traditional epidemiologic and contemporary clinical collections [21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…For instance there was one study using PheWAS in African Americans, linked to de-identified EHR data and mitochondrial SNPs[16]. Further, clinical laboratory variables can be used in high-throughput association with an array of diagnoses to identify important clinically relevant biomarkers.…”
Section: Moving Beyond Snpsmentioning
confidence: 99%
“…PheWAS is now being extended to explore the relationship between other genetic variation, such as the relationship between copy-number variation and a wide range of measurements, as well as the relationship between mitochondrial variation and outcome [16]. PheWAS can be used with common frequency SNPs, but also can be applied to low-frequency variation as more and more tools for using low frequency variants are being introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the utility of EHR data has exponentially grown for genomic studies from understanding the underlying biology of complex diseases to novel drug targets and their side effects[1316]. The genetic component of PheWAS is not limited to SNPs; we can use structural variations (copy number variations), mitochondrial variation[17], gene regions for low-frequency and rare variants (population allele frequency < 1%)[18] as well as non-genetic measures such as clinical laboratory measures[19] and quantitative measures derived from biomarkers.…”
Section: Introductionmentioning
confidence: 99%